UNDERSTANDING POLITICAL AND ECONOMIC TRANSITION IN POST-YUGOSLAV SERBIA AND SLOVENIA - Pinteric, Uros (Torun International Studies, 2018)
Article is short review of political and economic transition period in the area of former Yugoslavia. Author compares two of its most important parts, Serbia as previous political centre and Slovenia as economically most advanced republic that also tried to democratize Yugoslavian federation already before Yugoslav disintegration. Author argues that transition in Slovenia started much earlier than only in the late eighties of previous century and at the same time he is trying to find comparatively how far Serbia and Slovenia are with transition process after more than 15 years later. According to the current situation analyzed in the comparative perspective Serbia has great potential for not only complete transition, but also to become centre of South-Eastern Europe.